Denmark-Greenland in the twentieth century - Kjær Sørensen, Axel (Museum Tusculanum Press, 2012)
This book traces Danish-Greenlandic relations over 100 years and is the first publication to cover the period 1900-2000. The main trend is the development from a colonial situation in 1900 with a state owned company runnig nearly all business to an open economy with steadily growing selfgovernment for Greenland short of full independence. The Danish policy can be described as benevolent, but financially the budget was tight until after the second World War, the philosophy being that Denmark should neither lose nor gain. After the war there was heavy investment to bring Greenland nearer to standards of living comparable to Denmark and substantial subsidies were given make that happen. The Greenlanders attitude towards Denmark developed along lines familiar from other examples of decolonisation. The first phase of accepting the coloniser was long over, now seeking equality with the coloniser was the main aim in their endeavours. From 1911 two provincial councils woiced speaking the Greenlanders views and their political influence steadily grew. In 1953 Greenland got representation in the Danish parliament. The third phase of doing without the coloniser began in the early 1970s when Greenlanders sought home rule status, obtained in 1979. In the following twenty years the Home Rule Authority gradually took over nearly all lawmaking and administration and from 2004 a committee has explored ways of giving Greenland a more independent voice in foreign affairs. In 2003 the ultimate goal was declared to be full independence.